2011
DOI: 10.1111/j.1939-165x.2011.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pathology ofGreyhounds and other sighthounds

Abstract: Owing to the development of Greyhounds as racing sighthounds, these dogs have acquired unique physiologic adaptations that distinguish them from other breeds. Reference intervals for many analytes in retired racing Greyhounds (RRGs) differ from those of other breeds; most of the hematologic differences have also been described in other sighthounds. In this review, we provide a survey of the literature on clinical pathology of Greyhounds and other sighthounds and results of laboratory testing, including analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
156
4
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(182 citation statements)
references
References 50 publications
17
156
4
5
Order By: Relevance
“…Ilkiw et al (1989) suggested that hypoglobulinemia could be the result of plasma volume expansion associated with training; however, this theory does not explain why hypoglobulinemia is also present in sighthounds without training (Pape et al 1984). Nowadays, an adaptive mechanism to decrease serum viscosity in these breeds with higher haematocrit and blood viscosity is considered the most likely cause of low globulin concentrations in sighthounds (Bodey and Rampling 1998;Fayos et al 2005;Zaldívar-López et al 2011a). Nevertheless, the globulin fractions involved in the lower total globulin concentration do not seem to be the same in each sighthound breed; while in Greyhounds the lower total globulin concentration seems to be related to lower α-and β-globulin fractions (Fayos et al 2005); in Galgos in our study, the lower total globulin concentration was related with lower α2-and γ-globulins.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Ilkiw et al (1989) suggested that hypoglobulinemia could be the result of plasma volume expansion associated with training; however, this theory does not explain why hypoglobulinemia is also present in sighthounds without training (Pape et al 1984). Nowadays, an adaptive mechanism to decrease serum viscosity in these breeds with higher haematocrit and blood viscosity is considered the most likely cause of low globulin concentrations in sighthounds (Bodey and Rampling 1998;Fayos et al 2005;Zaldívar-López et al 2011a). Nevertheless, the globulin fractions involved in the lower total globulin concentration do not seem to be the same in each sighthound breed; while in Greyhounds the lower total globulin concentration seems to be related to lower α-and β-globulin fractions (Fayos et al 2005); in Galgos in our study, the lower total globulin concentration was related with lower α2-and γ-globulins.…”
Section: Discussionmentioning
confidence: 92%
“…Healthy Greyhounds have low total serum globulin concentrations due to low α-and β-globulin fractions (Fayos et al 2005). It was previously hypothesised that, because of the apparent shared ancestry (Parker et al 2007), laboratorial differences in Greyhounds might be extrapolated to other sighthound breeds (Zaldívar-López et al 2011a). However, recent studies suggest that the extrapolation of the Greyhound clinicopathological features to other sighthound breeds could lead to misdiagnoses (Uhrikova et al 2013;Sheerer et al 2013).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Changes in the haematology for different dog breeds have been documented. Separate referential values were established for Greyhounds, which have higher haematocrit (HCT), mean cell volume (MCV) and haemoglobin (HGB) concentration and a lower total platelet count (PLT) and total white blood cell (WBC) count compared to other breeds (Porter and Canaday 1971;Sullivan et al 1994;Guyton and Hall 2006;Campora et al 2011;Zaldivar-Lopez et al 2011). Physiological macrocytosis was diagnosed in miniature breeds and standard poodles (Schalm 1976).…”
mentioning
confidence: 99%